Leishmaniasis in the middle East: incidence and epidemiology. - Nasir Salam; Waleed Mohammed Al-Shaqha; Arezki Azzi (Public Library of Science (PLoS), 2014)
Leishmaniasis is a major health problem worldwide, with several countries reporting cases of leishmaniasis resulting in loss of human life or a lifelong stigma because of bodily scars. The Middle East is endemic for cutaneous leishmaniasis, with countries like Syria reporting very high incidence of the disease. Despite several countries establishing national control programs for containing the sandfly vector and treatment of infection, the disease continues to spread. In addition to the endemicity of the region for leishmaniasis, the Middle East has seen a great deal of human migration either for earning of livelihood or due to political upheaval in the region. These factors contribute to the spread and proliferation of the causative species Leishmania and its sandfly host. This review discusses the current epidemiological scenario in Iraq, Syria, Saudi Arabia, and Jordan, emphasizing the number of cases reported, vector species, Leishmania species, and treatment available. The data is primarily from WHO reports for each country and current and old literature.